2022
DOI: 10.1002/smll.202106412
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Cobalt Oxide/Carbon Hybrids Aid Metabolic Encoding for Active Systemic Lupus Erythematosus during Pregnancy

Abstract: A noninvasive, easy operation, and accurate diagnostic protocol is highly demanded to assess systemic lupus erythematosus (SLE) activity during pregnancy, promising real‐time activity monitoring during the whole gestational period to reduce adverse pregnancy outcomes. Here, machine learning of serum metabolic fingerprints (SMFs) is developed to assess the SLE activity for pregnant women. The SMFs are directly extracted through a hollow‐cobalt oxide/carbon (Co3O4/C)‐composite‐assisted laser desorption/ionizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Favorable optical properties are among the preconditions for the MALDI matrix, which can promote subsequent energy transfer and charge transfer. 39,40 It has been reported that complex multiple-shelled hollow structures show enhanced performance over conventional simple hollow structures owing to the improved light absorption properties from the scattering and reflection effects. 41,42 The influence of shell number on the LDI performance of ZMO/CMO was further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Favorable optical properties are among the preconditions for the MALDI matrix, which can promote subsequent energy transfer and charge transfer. 39,40 It has been reported that complex multiple-shelled hollow structures show enhanced performance over conventional simple hollow structures owing to the improved light absorption properties from the scattering and reflection effects. 41,42 The influence of shell number on the LDI performance of ZMO/CMO was further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[42] Furthermore, hybrid materials of metal oxides can introduce diverse components, resulting in efficient carrier transport for enhanced ionization efficiency of small metabolites and abundant metal sites for specific extraction of proteins/peptides. [44,46] Vedarethinam et al constructed vanadium oxide core-shell nanorods (SiO 2 @V 2 O 5 ) using mesoporous silica nanorods to support vanadium oxide on the surface for metabolic detection. Besides, mesoporous silica with tuneable pore size and high surface area realized effective adsorption of small molecules.…”
Section: Metal Oxide Nanomaterialsmentioning
confidence: 99%
“…Combining the optimized algorithm, the diagnostic models successfully discriminated pregnant patients with active systemic lupus erythematosus (SLE) from the inactive SLE and healthy controls (HC) with simple, accurate, and cost-effective measures. [46] Huang et al developed a multifunctional Pt-based nanoreactor platform for high-throughput profiling of metabolite fingerprints in the native serum. As a result, the platform identified a panel of five biomarkers, allowing for the differentiation of pancreatic cancer patients from healthy controls to be successfully diagnosed, with a sensitivity of 84% and specificity of 92%.…”
Section: Untargeted Metabolic Fingerprints Analysis In Biological Fluidsmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization time of-flight (MALDI-TOF) MS possesses competitive advantages in fast analysis, simple sample preparation, high-throughput, low cost, and accurate mass measurement for metabolic-based disease screening compared to the above-mentioned techniques. Notably, the matrix with rational design acts in a significant role in the small metabolic analysis of LDI-TOF MS . Based on the unique physicochemical properties of nanomaterials, various inorganic materials have been served as MALDI matrices for the analysis of small molecules. Particularly, carbon-based nanomaterials including fullerene, graphene, and carbon nanotube, with attractive structural feature and high ultraviolet (UV) absorption, have been extensively employed for detecting various small molecules, even in vitro diagnostics application .…”
Section: Introductionmentioning
confidence: 99%